Brand Loyalty-Building Strategy: Influence Product Quality, Perceived Experience Quality, And Brand Attitude Through Mediating Brand Trust - Pramadanti, Rindika (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2025)
Research aim: This study aims to measure product quality, perceived experience quality, and brand attitude that can affect brand trust through brand loyalty to Janji Jiwa coffee products. Methode: Data will be collected using a survey method and questionnaires. This study used Structural Equation Modeling (SEM) data analysis techniques operated using the Smart-PLS program version 3.2.9 Theoretical contribution: This research also proves that product quality and perceived experience quality can affect brand trust, while brand attitude influences brand loyalty. It aims to create a sense that customers expect to be able to compete with other competitors in the future. Practitioner implication: Product quality, perceived experience quality, and brand attitude play an important role in increasing brand trust and brand loyalty, where good taste integrity and customer expectations will affect growing sales, so coffee shop entrepreneurs must provide innovation strategies in maintaining product quality to influence consumers to be loyal to their products. Research limitation: This study only focuses on three variables: product quality, perceived experience quality, and brand attitude